The Effectiveness of Nursery Rhymes Media to Improve English Vocabulary and Confidence of Children (4-5 Years) in Tutor Time Kindergarten - Christina, Yuni; Pujiarto, Pujiarto (Journal of Education Research, 2023)
This study aims to evaluate the effectiveness of using nursery rhymes as media in increasing English vocabulary and self-confidence in children aged four and five years at Tutor Time Kindergarten, an Early Childhood Education school. Five English nursery rhymes are used to teach vocabulary to children. This study also examines the increase in children's confidence in singing and speaking English in public. This research method is an experiment with the control group and the treatment group. The results showed that the use of nursery rhymes as media was effective in increasing English vocabulary in children aged four and five years. Children in the treatment group showed a significant increase in understanding and using new vocabulary after participating in song learning. In addition, this study also revealed that there was an increase in children's confidence in singing and speaking English in public after they were involved in learning to use these songs. The use of nursery rhymes as media is an effective approach in increasing English vocabulary and self-confidence of early childhood at Tutor Time Kindergarten. These results have important implications for the development of fun and interactive learning methods in the PAUD environment to facilitate children's language development and confidence in English.